Superbrotamento ou floco da mandioca. Identificacao e controle - Empresa de Asistencia Técnica e Extensao Rural do Ceará; Empresa de Pesquisa Agropecuária do Ceará; International Center for Tropical Agriculture (Empresa de Pesquisa Agropecuária do Ceará (EPACE), 1988)
To help farmers identify the disease, the symptoms of witches` broom are described and illustrated. A serious disease of cassava in the state of Ceara, Brazil, it has caused yield reductions of over 60 percent. All diseased material should be burned. To control the disease, healthy planting material should be used. (CIAT)